(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The main goal of the study is to find out how tourists’ opinions of how the front desk worked at the hotel affected how happy they were with their stay and how likely they were to return to one of Kashmir’s five-star hotels. A structured questionnaire was given to 500 visitors as part of this study to find out what they thought about the front desk, the level of service, and their general happiness. The research method used was both descriptive and analytical. The results show that customers are most satisfied when staff members are polite, personal information about guests is kept private, and check-in and check-out times are kept on time. People have pointed out that custom deals and hotel changes need to be made available more often. The study stresses how important it is to offer personalized services, run processes efficiently, and have skilled staff in order to make customers happier and more faithful. Some suggestions for better hotel management include giving employees more chances to learn and grow, making communication better, streamlining operations, and giving guests more options. From the guests’ point of view, this study adds to the field of hospitality by showing what the front desk does in Kashmiri hotels. This study talks about the goals of Kashmir’s star hotel group and focuses on how the front desk is thought to affect customers’ general happiness.